Analisis Strategi Penerjemahan Idiomatik Dalam Novel “ARTEMIS” Karya Andy Weir - Amalia, Ikeu Nur; Dewi, Ika Sari (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2024)
Idioms are one of the most commonly used figurative expressions in literary works, and they are often referred to as a problem that machine translators can never solve. This study aims to discover the strategies used in translating idioms in the novel